Hyperglycaemia in the Newborn Infant. Physiology Verses Pathology - Beardsall, Kathryn (Frontiers in Pediatrics, 2021)
Hyperglycemia is common in newborns requiring intensive care, particularly in preterm infants, in sepsis and following perinatal hypoxia. The clinical significance, and optimal intervention strategy varies with context, but hyperglycaemia is associated with increased mortality and morbidity. The limited evidence for optimal clinical targets mean controversy remains regarding thresholds for intervention, and management strategies. The first consideration in the management of hyperglycaemia must be to ascertain potentially treatable causes. Calculation of the glucose infusion rate to insure this is not excessive, is critical but the use of insulin is often helpful in the extremely preterm infant, but is associated with an increased risk of hypoglycaemia. The use of continuous glucose monitoring (CGM) has recently been demonstrated to be helpful in targeting glucose control, and reducing the risk from hypoglycaemia in the preterm infant. Its use in other at risk infants remains to be explored, and further studies are needed to provide a better understanding of the optimal glucose targets for different clinical conditions. In the future the combination of CGM and advances in computer algorithms, to provide intelligent closed loop systems, could allow a safer and more personalized approached to management.